Modificación de librería de control para mejorar interacción de robot con el entorno - Ruiz Jara, Jose Antonio (2020)
One of the objectives of the Poppy Project is to offer a platform accessible to beginners andexperts, allowing robots to be used in multiple fields, including research and teaching.During the work with Pypot, the control library in charge of controlling the Poppy robots, severallimitations have been detected that are needed to be fixed. One of the most important problemrelated to the research work that is going to be done, is the small number of sensors that it canaccess.Thanks to the fact that both software and hardware are open source and the users can adjustthem to their needs, a series of modifications are intended to be done on the control library,to use the humanoid robot Poppy in the research project. One of the main requirements is thecapacity to use via Pypot the new sensors and actuators added to the robot.Finally, in a period of four months of work, the library got improvements in the image processingmodule, communication with IMU and Arduino boards, implementation of facial recognition, useof proximity sensors in simulation, use of custom motors in simulation, simultaneous executionof instructions in multiple robots, display of animations through the LCD screen, and a behaviorcontroller that allows combining more than one functionality to create behaviors.